The Influence of Brand Awareness and Brand Attitude on Purchase Intention of Riau Malay Woven Products “Puteri Mas” in Bengkalis City - Sari, Rini Arvika; Handayani, Tri; Mawarni, Sri (Politeknik Negeri Bengkalis, 2024)
The purpose of this study is to examine the influence of brand awareness and brand attitude on purchaseintention towards Riau Malay woven products